Factor H family proteins: on complement, microbes and human diseases. (November 2002) - Zipfel, P. F.; Skerka, C.; Hellwage, J.; Jokiranta, S. T.; Meri, S.; Brade, V.; Kraiczy, P.; Noris, M.; Remuzzi, G.
Abstract : At present, the human Factor H protein family represents seven multidomain, multifunctional serum proteins. This group includes the complement and immune regulators Factor H, the Factor H-like protein 1 (FHL-1) and five Factor H-related proteins proteins (FHR-1, -2, -3, -4 and -5). Each is exclusively composed of individually folded protein domains, termed short consensus repeats (SCRs) or complement control modules. Structure-function analyses allowed the localization of the complement regulatory domain of Factor H and FHL-1 in the N-terminal region within SCRs 1–4. In addition, multiple binding sites for C3b, heparin and microbial surface proteins were localized in the N-terminus, within the middle region and also in the C-terminus of Factor H and FHL-1. Recent results show a central role for the C-terminus of Factor H, i.e. SCRs 19–20. These particular domains are conserved in all FHRs identified so far, include contact points for C3b, heparin and microbial surface proteins and represent a 'hot-spot' for gene mutations in patients that suffer from the Factor H-associated form of haemolytic uraemic syndrome.